Methodological guidelines for the practical work in the discipline "Innovative Entrepreneurship and Management of Startup Projects" - Litvinova, Uliya Sergiivna (National Technical University "Kharkiv Polytechnic Institute", 2025)
The main stimulating element of the growth of any modern market-type economy is the development of small and medium-sized businesses. It is small and medium-sized businesses that today ensure the formation of the middle class, which is increasingly becoming a pillar of the society of any country. At the same time, it should be noted that the development of this sector of the economy requires the spread and support of youth entrepreneurship, which in turn contributes to the professional and personal self-realization of young entrepreneurs, improving their financial situation, gaining diverse experience and solving the problem of employment. Three interacting forces play a key role in supporting young entrepreneurs: the state; the agreement; universities. To increase the effectiveness of supporting youth entrepreneurship, these segments must closely cooperate. During the course, students will have the opportunity to create their own projects and submit them to the startup competition. The workshop is designed to combine the applicant's independent work with work in lectures and practical classes. The workshop presents tasks, business games, questions for self-testing, and a list of recommended literature. In order to master theoretical knowledge on each topic, practical tasks are provided that relate to the corresponding stage of creating your own startup. There is also the opportunity to develop prototypes of your ideas, conduct surveys and participate in business games. This ensures independent learning, promotes in-depth and comprehensive study of the academic discipline "Innovative Entrepreneurship and Startup Project Management", gives the opportunity to learn how to quickly and correctly navigate the source information and solve important issues related to innovative entrepreneurship in general and the creation and management of a startup in particular. The calculation task is drawn up in the form of a report; all calculations must be provided.
Keywords: methodological guidelines; calculation; innovation; management; calculation of net discounted income; calculation of Payback Period; discounted income